The Evaluatıon Of Bond Strength Of Dırect-Bondıng Fıxed Space Reatıners - Hüseyin Ölmez; Faik Korunmuş; Seval Ölmez (Galenos Yayinevi, 1994)
In this study the bond strength affixed space retainers, is examined. Investigation is carried on in vitro, and 20 first molars and 20 deciduous second molars were embedded in self-curing acrylic blocks by the help of parallelometer. Then, fixed space retainers were bonded on each teeth in equal conditions. Compression forces were applied on all teeth using Instron testing machine. The results were analyzed by means of the biostatistical analyzing system.